Teacher's emphatic communication to improve learning motivation of special needs students - Choirul Fajri (International Journal of Communication and Society, 2020)
This study aims to analyze how the role of teachers in increasing their interest in learning, especially in relation to empathy communication patterns that are run. The research method used in this research is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and literacy studies. The Indonesian government has guaranteed equal rights to the fulfillment of education for all Indonesian citizens including children with special needs. Based on data from the Central Statistics Agency, until 2017 the number of children with special needs in Indonesia reaches 1.6 million. From this data, it is seen the need for maximum efforts to achieve the goals of inclusive education and the fulfillment of the right to education for children with special needs in Indonesia. In fact, on the ground it appears that the practice of inclusive education for several years is inseparable from various obstacles and problems. The results of this study indicate that empathy communication is effective in increasing the learning interest of students with special needs. The teachers use various strategies in the learning process to increase their interest in learning.